Improved management of vertisols for sustainable crop-livestock production in the Ethiopian highlands: Synthesis report 1986-92 - Mamo, T.; Astatke, A.; Srivastava, K.L.; Dibabe, A. (Technical Centre for Agricultural and Rural Cooperation, 1993)
Some of the papers in this report deals with nutrient management; land, soil and water management; grain, fodder and residue management; and technology validation and transfer. The other papers looks into development of coordinated research efforts; distribution and importance of Ethiopian vertisols and locations of study sites; a survey of the farming systems of Vertisol areas of the Ethiopian highlands, and modifying the management of vertisols. The report ends with a discussion on retrospect and prospects of the Joint Project on Vertisols management.